PROSEDUR PEMBAYARAN UTANG KEPADA VENDOR OLEH ACCOUNT PAYABLE DI ADIWANA HOTELS & RESORTS - Sutrisnawati, Ni Ketut; I Made Agus Deprianto; Ni Gusti Ayu Nyoman Budiasih (Jurnal Kajian dan Terapan Pariwisata, 2024)
The accounting department, especially accounts payable, plays an important role in keeping the hotel's operations running smoothly. One of those roles is to establish good cooperative relationships with external parties of the hotel, namely vendors. Adiwana Hotel & Resorts is a hotel located in Ubud, Bali. One of the efforts made by Adiwana Hotel & Resorts to create good cooperation with vendors is to implement a good debt payment procedure between the hotel, Adiwana Hotel & Resorts, and the vendors. The debt payment process that follows the procedure will smoothen operations at Adiwana Hotel & Resorts. This research aims to analyze the debt payment procedures to vendors by accounts payable at Adiwana Hotels & Resorts. Data were obtained through observation, interviews, and documentation, then analyzed using qualitative descriptive methods. The procedure for debt payment to vendors at Adiwana Hotels & Resorts begins with the purchasing process, followed by receipt, and concludes with the payment process to the vendor. The debt payment process is handled by the accounting department, which involves the purchasing, receiving, and payment sections. The debt payment process requires documents including Purchase Requisition, Purchase Order, Receiving Report, Sales Invoice, Tax Invoice, Bank Payment Voucher, and Receipt. Good cooperation is required between sections in the accounting department and other departments involved in purchasing and receiving goods so that the necessary documents can be completed on time, allowing debt payments to be carried out according to procedure.